2001
DOI: 10.2175/193864701785019245
|View full text |Cite
|
Sign up to set email alerts
|

Problems in Dairy Wastewater Treatment

Abstract: Operational data from nine dairy wastewater plants in Wisconsin were collected and analyzed to determine reasons for frequent deterioration of biological phosphorus removal (BPR) efficiency and to optimize BPR for various wastewater treatment processes. Several major factors affecting BPR were identified from the data obtained from dairy wastewater treatment plants. First, many dairy wastewater treatment plants suffer low F/M ratios during off-days, leading to sludge bulking and unstable and poor BPR efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Therefore, higher wastewater temperature could be expected (>208C). Besides, the dominance of GAO has also been reported in WWTP handling warm industrial effluents (where wastewater temperature is higher than 278C) (Jobbàgy et al, 2002;Park et al, 2001). At lab-scale, different researchers have studied the temperature effects on the biological phosphorus removal (BPR) process to explain the effects of temperature on the PAO-GAO competition (Erdal et al, 2003;Panswad et al, 2003;Park, 2002, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, higher wastewater temperature could be expected (>208C). Besides, the dominance of GAO has also been reported in WWTP handling warm industrial effluents (where wastewater temperature is higher than 278C) (Jobbàgy et al, 2002;Park et al, 2001). At lab-scale, different researchers have studied the temperature effects on the biological phosphorus removal (BPR) process to explain the effects of temperature on the PAO-GAO competition (Erdal et al, 2003;Panswad et al, 2003;Park, 2002, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of temperature on P removal mechanisms and PAO metabolism are still unclear, and some are even contradictory as a result of incomparable experimental designs. Park et al [15] observed a significant seasonal effect on EBPR in a wastewater treatment plant with poor EBPR efficiency during the summer, when the wastewater temperature was approximately 30 • C. At water temperature states less than 10 • C, EBPR was reported to be inhibited [16,17]. In some other studies [18,19], better EBPR performances were observed at lower temperature (5 • C) than at higher temperatures (10 and 15 • C).…”
Section: Introductionmentioning
confidence: 98%